Nanobugs as Drugs: Bacterial Derived Nanomagnets Enhance Tumor Targeting and Oncolytic Activity of HSV‐1 Virus. Issue 13 (25th January 2022) - Howard, Faith H N; Al‐Janabi, Haider; Patel, Priya; Cox, Katie; Smith, Emily; Vadakekolathu, Jayakumar; Pockley, A. Graham; Conner, Joe; Nohl, James F; Allwood, Dan A; Collado‐Rojas, Cristal; Kennerley, Aneurin; et al.
Abstract: The survival strategies of infectious organisms have inspired many therapeutics over the years. Indeed the advent of oncolytic viruses (OVs) exploits the uncontrolled replication of cancer cells for production of their progeny resulting in a cancer‐targeting treatment that leaves healthy cells unharmed. Their success against inaccessible tumors however, is highly variable due to inadequate tumor targeting following systemic administration. Coassembling herpes simplex virus (HSV1716) with biocompatible magnetic nanoparticles derived from magnetotactic bacteria enables tumor targeting from circulation with magnetic guidance, protects the virus against neutralizing antibodies and thereby enhances viral replication within tumors. This approach additionally enhances the intratumoral recruitment of activated immune cells, promotes antitumor immunity and immune cell death, thereby inducing tumor shrinkage and increasing survival in a syngeneic mouse model of breast cancer by 50%. Exploiting the properties of such a nanocarrier, rather than tropism of the virus, for active tumor targeting offers an exciting, novel approach for enhancing the bioavailability and treatment efficacy of tumor immunotherapies for disseminated neoplasms. Abstract : The development of a bacterial derived magnetic delivery system demonstrates a multifunctional approach to enhancing the efficacy of oncolytic viruses for the treatment of breast cancer, providing a safe carrier, an active targeting component, and an improved exposure profile.